SÍNTESE DE NANOTUBOS DE CARBONO PELA TÉCNICA DE DEPOSIÇÃO CATALÍTICA QUÍMICA EM FASE VAPOR - Fischer, Marcel Vinícius Theisen (2010)
The carbon nanotubes (CNT) are small cylinders with diameters in order of nanometers (10-9 m) and, of some micrometers (10-6 m) of length. Carbon nanotubes are conceptually built considering the rolling up of a strip of graphene sheet. The electronic, mechanical, and optical properties of the tube depend on how the graphene sheet is rolled up. More than one graphene sheet can be rolled up forming concentric nanotubes which are called multiple walled carbon nanotubes (MWCNT). The knowledge and parameterization of synthesis methods are of extremely importance for the development of carbon nanotubes science. This work had as objective the installation of a system for CNT production, using chemical catalytic vapor deposition (CCVD), and the evaluation of the effects of synthesis parameters in formation of carbon nanotubes. In this work, parameters such as temperature and time of synthesis using three kinds of catalysts (Fe/MgO, Fe/Al2O3 e Co/Al2O3) were investigated keeping the catalyst mass fixed in 100 mg. The temperatures varied from 750 to 850 °C and synthesis time from 10 to 15 minutes. During the process, an argon flow of 1,0 L/min was used to maintain an inert atmosphere in the tube furnace. When the programmed temperature was reached, a flow of ethylene gas (0,1 L/min-1) was inserted in the reactor. When finishing the synthesis time, gases flux were interrupted. The samples were characterized by Raman spectroscopy. The best synthesis temperature was 800°C for catalysts Fe/MgO and Fe/Al2O3, using 750 °C and Co/Al2O3 catalysts during 15 minutes. The mass medium gain of CNT produced, without purification, was of 112%. The proposed system presented satisfactory results in relation to NTC production in laboratorial scale and the choose of synthesis parameters lead to the synthesis of different CNTs.